Antibacterial Activity Test and Wound Healing Infection Telang Leaf Extract (Clitoria ternatea L.) in Hyperglycemic Rabbits - Arif Wijayanto; Juvita Herdianty; Adjie Wahyu Pradana (Strada Journal of Pharmacy, 2022)
This study was conducted to determine the antibacterial activity and wound healing of Telang (Clitoria ternatea L.) leaf extract against Staphylococcus aureus ATCC 25293 and Escherichia coli ATCC 25922 in 15 New Zealand rabbits aged 3-5 months weighing 1500–2500 grams of hyperglycemia induced by alloxan and randomly divided into 5 groups, namely normal, negative control (cream base), positive control (Sagestam® which each gram contains Gentamycin Sulfate equivalent to 1 mg of Gentamycin), topical administration of 10% and 20% Telang leaf extract cream. The back skin of the hyperglycemic rabbit was injured with a punch biopsy with a diameter of 5 mm, a depth of ± 0.5 mm, then treated according to the test group for 14 days. Parameters measured included wound diameter and histological observations of infected and non-infected wounds in hyperglycemic rabbits. The results showed that 10% Telang leaf extract cream had antibacterial activity against S. aureus and E. coli which was comparable to the positive control, namely the diameter of the inhibition zone against S. aureus and E. coli was 27.3mm and 18.5mm. Telang leaf extract cream also had infection wound healing activity which was comparable to positive control in hyperglycemic rabbits, wound healing activity for infected wounds was 0.9 mm and non-infected wounds were 0.8 mm.